ANALYSIS OF COMMUNITY AND CONTENT STRATEGIES ON BUSINESS GROWTH THROUGH BRAND IMAGE AS AN INTERVENING IN MEDAN CITY'S TYPICAL SOUVENIRS - Bunga Aditi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
In increasing the growth of creative businesses, it is necessary to create a targeted strategy by adjusting market conditions. The growth of the Medan city souvenir business is increasingly famous, this is indicated by the many communities that share the same liking for Medan souvenirs and the existence of content as an action to increase promotion and brand image. regional business. The purpose of this study is to examine and analyze community and content strategies for business growth through brand image as an intervening variable in Medan city souvenirs. The results of the study show that the Community has a significant effect on brand image, partially the Community does not have a significant effect on Business Growth, partially Content has a significant effect on Brand Image, partially Content has a significant effect on Business Growth and partially brand image has a significant effect on Business Growth meaning the direction of the influence is positive. Brand image as an intervening variable has a significant impact on increasing the influence of the Community on Business Growth. Brand image as an intervening variable has a significant impact in increasing the influence of Content on business growth.